PENERAPAN PROGRAM MENTORING CLASS SEBAGAI UPAYA MEMPERKUAT SELF-ESTEEM SISWA DI SMP BUMI CENDEKIA YOGYAKARTA - Kartika, Nadia Raifah Nawa; Apriliani, Titi (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2023)
This research aims to find out and describe the Mentoring Class program and its impact on increasing students' self-esteem at SMP Bumi Cendekia Yogyakarta. This research uses a qualitative approach with a descriptive research design. Data collection techniques are carried out through interviews, observation and documentation. The results of the research show that Mentoring Class program at SMP Bumi Cendekia Yogyakarta has positive impacts on strengthening students' self-esteem. The themes and material presented also reflect the three main aspects of self-esteem, namely performance, social and physical self-esteem. Aspects of performance and physical self-esteem are reflected in material related to self-love. In addition, the social aspect of self-esteem is reflected in material that discusses boundaries in joking, bullying, friendship relations, etc. Mentoring Class program provides students a sense of security and comfort to speak up or convey their problems to the mentor which ultimately leads to increase self-confidence, independence, self-acceptance, and respect for others.